A Work Environment Under Pressure: Psychosocial Job Demands and Resources Among Saturation Divers - Romsbotn, Siri; Eftedal, Ingrid; Vaag, Jonas Rennemo (Frontiers in Public Health, 2022)
Saturation divers work and live under high physiological and social demands for weeks on end. Even though physiological research has contributed insights to the work conditions of saturation divers, research on the qualities of the divers' psychosocial work environment is lacking. This study aimed to explore which job demands and resources are viewed as characteristic among saturation divers working within an isolated and confined environment. Based on data from 6 in-depth semi-structured interviews, template analysis was applied to map unique characteristics. By using the theoretical framework of the job demands-resources model, we found that the work environment in saturation diving was characterized by shifting demands and big contrasts, requiring adaptability in each individual diver. One major demand described by the informants was an unpredictable future, somewhat due to the changes in the oil and gas industry. Another important demand was the conflict between family and work/leisure when committing to work for extended periods in isolated environments. The monotony that characterizes the work environment is a challenge that must be managed. High wages, periods of leisure, and a prestigious job provide external motivation, while personal resources such as mental endurance and flexibility, a willingness to learn, and keeping up small personal routines, may benefit the divers' mental health. This is also affected by the quality of team climate—with features such as being sociable and considerate, having a dark sense of humor and having trust in one another.